Risk-adjusted performance and market timing of Islamic equity mutual funds in Indonesia: A multi-model analysis - Yasir Maulana; Syed Iradat Abbas; Nurul Siti Jahidah; Hezah Nur Jannah (Faculty of Islamic Economics and Business, UIN Salatiga, 2025)
This study evaluates the risk-adjusted performance and market-timing ability of 40 Sharia equity mutual funds in Indonesia over the period from January 2021 to December 2023. Five models are applied: Sharpe Ratio, Treynor Ratio, Jensen’s Alpha, Modigliani-Modigliani (M²), and the Treynor-Mazuy model, using the Jakarta Islamic Index 70 (JII70) as the benchmark. All 40 funds underperformed the benchmark on a risk-adjusted basis, with universally negative Sharpe, M², Treynor, and Jensen’s Alpha values. The Treynor-Mazuy analysis shows that virtually no fund demonstrated statistically significant market-timing ability. These findings suggest that fund managers have yet to demonstrate consistent superior stock selection or timing skills during the post-pandemic recovery phase. For investors, these results underscore the importance of selecting funds based on risk-adjusted metrics. For fund managers, the findings call for enhanced active strategies and better integration of quantitative tools within Sharia constraints. For policymakers, stronger transparency standards for performance are needed. This study contributes to the Islamic finance literature by providing a multi-model empirical benchmark for Sharia equity fund performance in an underexplored market context